Job Displacement, Unemployment Benefits and Domestic Violence - Sonia Bhalotra; Diogo Britto; Paolo Pinotti; Breno Sampaio (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2021)
We estimate impacts of male job loss, female job loss, and male unemployment benefits on domestic violence in Brazil. We merge employer-employee and social welfare registers with administrative data on domestic violence cases brought to criminal courts, use of public shelters by victims, and mandatory notifications of domestic violence by health providers. Leveraging mass layoffs for identification, we first show that both male and female job loss, independently, lead to large and pervasive increases in domestic violence. Exploiting a regression discontinuity design, we then show that unemployment benefits do not reduce domestic violence while benefits are being paid, and that they lead to higher domestic violence once benefits expire. These findings can be explained by the negative income shock brought by job loss and by increased exposure of victims to perpetrators, as partners tend to spend more time together after displacement. Although unemployment benefits partially offset the income drop following job loss, they reinforce the exposure shock as they increase unemployment duration.
Keywords: 330: domestic violence; unemployment; mass layoffs; unemployment insurance; income shock; exposure; Brazil